2017
DOI: 10.1007/s13187-017-1209-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Breast Cancer: Knowledge, Attitude, and Practice of Family Health Strategy Women

Abstract: In rural area, control of breast cancer is related to health promotion and early diagnosis, which includes knowledge, awareness, and stimulating behavioral change, emphasizing screening for disease. The present study was developed to assess the knowledge, attitude, and practice of rural women about early detection of breast cancer in the Primary Health Care Centre. This is a cross-sectional study in a Primary Health Care Centre with 243 rural women participating in the public health service. Data collection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The people´s awareness of cancer and the stimulation of behavioral changes and research are fundamental actions for the initial prevention of cancer. This finding reinforces the importance of continuing education, so health professionals can competently develop the actions proposed by public cancer control policies (5)(6)(7) .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The people´s awareness of cancer and the stimulation of behavioral changes and research are fundamental actions for the initial prevention of cancer. This finding reinforces the importance of continuing education, so health professionals can competently develop the actions proposed by public cancer control policies (5)(6)(7) .…”
Section: Introductionsupporting
confidence: 61%
“…The knowledge, attitude and practice of the tests were assessed as follows: (1) adequate knowledge, when the woman reported having heard of early breast cancer screening exams (clinical examination of the breasts and mammography) and knew how these tests were performed and also how they were used for the early detection of the disease; (2) inadequate knowledge, when the woman said that she had never heard of the examinations or had heard, but could not quote it, how they should be performed, or what they were for; (3) adequate attitude when the woman reported that she should perform the tests and presented the early detection of breast cancer as the reason for performing these tests and/or when she referred as a reason to be a routine examination or desire to know if she was okay with it (self-care) -there was only considered an appropriate attitude when, at the same time, she had adequate knowledge of the examinations; (4) inadequate attitude: when the woman reported that she should not take the tests and did not have other motivations for the examination other than the early detection of breast cancer or self-care; (5) adequate practice in the clinical examination when the woman reported that she performed this examination annually and, the mammography, when the woman reported performing it annually or at least every 2 years. It is worth noting, as recommended (1) , that the mammography was valid for those over 35 years old; (6) inadequate practice when the woman had performed these tests in periodicities other than those mentioned above or had never performed them.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies from various countries, high educational level was one of the most important predictors of adherence to MS. [28][29][30][31] In agreement with our results, several Brazilian studies reported a greater chance of adherence to MS among women with higher educational levels. 5,8,27,32,33 In contrast, a recent study also performed in the Northeast region of Brazil, among women who had predominantly a low educational level, high income instead of education was associated with MS participation. 9 The nationwide adherence study by Narayan et al in the United States identified both high income and educational level as important predictors of adherence to MS. 29 Data of the present study also indicated that occupied women performed MS more often compared with those who were not occupied.…”
Section: Discussionmentioning
confidence: 90%
“…The fourth part of the questionnaire assessed the participant's CBE and mammography practices, based on questionnaires by de Oliveira et al and Wang J.H. et al [15,20]. In total, the questionnaire included 38 items, with a mix of multiple-choice and yes/no questions in addition to demographic data.…”
Section: Methodsmentioning
confidence: 99%